Surface Active Agents in Household Fabric Care Products - Z. Idris; Z. Abdul Maurad; H. Abd Aziz (Universiti Sains Islam Malaysia, 2024)
Surface active agents or surfactants are important class of compound in laundry detergent and fabric softeners as they are the key ingredient that determines the performance of the products. Anionic surfactants for laundry detergent and cationic surfactants for fabric softener both perform independently, can be derived from renewable vegetable based feedstock, namely, and saturated palm stearin fatty acid or methyl ester which provide equivalent carbon chain length as that of tallow based feedstock. Methyl ester sulphonate (MES), an anionic surfactant, has been prepared by a sulphonation process between palm stearin methyl ester and sulfur trioxide followed by bleaching and neutralization processes while quartenized triethanolamine ester or esterquats, a cationic surfactant, has been prepared either by the condensation reaction between fatty acid and triethanolamine or interesterification reaction between methyl ester and triethanolamine. The cationic property was provided on triethanolamine ester through a quaternization reaction by dimethyl sulfate. As a household fabric care products, these two surfactants meet the biodegradability criteria as they are being discharged into the sewarage systems. The two surfactants, when formulated into laundry detergent and fabric softeners, respectively, are branded under the 'PALM TOUCH' product series.